2004
DOI: 10.1111/j.1651-2227.2004.tb00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Snakebites in children in the densely populated city of Hong Kong: a 10‐year survey

Abstract: Aim: To review the pattern and characteristics of snakebites in children in rural Hong Kong. Methods: A retrospective chart review was conducted. Results: Seven cases of snakebite in children were reported. Eighty‐six percent of the victims were male, and the majority of bites (86%) occurred on the left extremities. Green pit vipers (Trimeresurus albolabris) accounted for most of the snakebites. Local symptomatology was common. Swelling, pain and fang marks were documented in all cases. A mildly deranged clott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…In Taiwan, despite rapid urbanization, snakebites occur often in adults who work on farms, in fields and in forests (7). However, as the habitats of snake species often overlap with human environments, children are occasionally bitten by snakes (8). Venomous snakebites are fatal for small animals but are generally not lethal in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, despite rapid urbanization, snakebites occur often in adults who work on farms, in fields and in forests (7). However, as the habitats of snake species often overlap with human environments, children are occasionally bitten by snakes (8). Venomous snakebites are fatal for small animals but are generally not lethal in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Venomous snakebites are typically associated with marked oedema and pain within an hour of envenomation (3,4). Haemorrhage and necrosis are common, and paired bite marks are often noted (3). Compartment syndrome occasionally develops in the bitten limb (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Snakebite injuries in children and young persons have become uncommon in the metropolitan, densely populated city of Hong Kong (1–4). We previously reported a 10‐year survey of snakebites in children and concluded that children should be discouraged to play in areas where snakes may hide, and that protective footwear should be worn (3). Snakebites are rarely fatal but may cause significant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Bamboo snake, as with other species of the family Viperidae, causes local wound complications and coagulopathy. The family Elapidae includes cobra (Naja) as one of the genus.…”
Section: Discussionmentioning
confidence: 99%